Rheological Characterization of Polyoxyethylene (Poe) and Carboxymethyl Cellulose (Cmc) Suspensions with Added Solids - Osorio-Lira, F (Institute of Physics Publishing, 2015)
The rheological properties of high molecular weight POE and CMC suspensions by adding micro-metric solid particles such as fibers or spheres were studied. The volume fraction, Φ, was varied between 0 and 0.4. Their rheological properties were obtained after fitting a Cross model. For POE suspending fluid with spherical particle, the behavior of the normalized steady shear viscosity, μ/μ0, as function of the fraction volume followed a Thomas model. However, for CMC suspensions, μ/μ0 seems to be lineal with Φ. For a pure fluid or a suspension with Φ = 0; 2, the suspension presented an elastic behavior whereas it was observed a viscous behavior when the volume fraction was increased. © Published under licence by IOP Publishing Ltd.